The theme, style, and humor Malaysian popular magazines in Malaysia Gila – Gila, Ujang and Gempak (1978 – 2015) / Mohamad Kamal Abd Aziz, Nor Nadhirah Aniqah Abd Rahim and Arbaiyah Ab. Aziz - Abd Aziz, Mohamad Kamal; Abd Rahim, Nor Nadhirah Aniqah; Ab. Aziz, Arbaiyah (Faculty of Art and Design, 2022)
Due to the emergence of digital technology and the popularity of social media, many local cartoon magazines, including Ujang and Gempak, have ended their publications. The decline is because people have many options and access to digital and free cartoons. The inclination and tendency to change from the sociocultural aspect affect the cartoon theme, style, and humor. This study aims to critically analyse the style, theme, and humor of cartoons in magazines like Gila-Gila, Ujang, and Gempak. This study was conducted through contextual analysis of the selected samples of cartoons. Feldman’s method of art criticism comprising the strategies of description, analysis, interpretation, and judgment and Gombrich’s theory of style were applied to the cartoons. The Gila-Gila cartoonist selected for this research is Rejabhad. The cartoonists from Ujang and Gempak are Sukun and Zuan, respectively. The findings of this study show that each cartoonist has his style, theme, and humor while instilling sociological, cultural, economic, and religious aspects as well as having the Malay and Malaysian essence. Humor can be generated by many methods either in communication or persuasion. Therefore, in the future, it may strengthen the role of cartoons and cartoonists in the new publications of local cartoon magazines.